The historical link between China and Peru since 1590 in the framework of "La Franja Y La Ruta" - Coaricona Mendoza, Rosa (2021)
This research investigates the historical link between China and Peru that dates back to the year 1590, where the first Chinese citizens would arrive at the Port of Callao and from that moment on they would establish their domicile on the Pacific coast, making their culture known. it has been built and cultivated within the Peruvian customs. In 1590 Peru was under the rule of the Spanish, who established the Central Viceroyalty of Spain in Lima, known as the city of the Kings. In the same way, it is desired to provide historical data of the journey of the first mestizo woman named Isabel Barreto, who left the port of Callao in Peru towards the Continent of Asia, crossing the Pacific Ocean with a boat of 380 people on board, historical novel narrated by the Peruvian diplomat Ernesto Pinto Bazurco Rittler. On the other hand, there is also the story about the journey of Tupac Inca Yupanqui, who arrived in Polynesia a century before, than Isabel Barreto.